Nitrosative Stress in the Frontal Cortex From Dogs With Canine Cognitive Dysfunction - Prpar Mihevc, Sonja; Zakošek Pipan, Maja; Štrbenc, Malan; Rogelj, Boris; Majdič, Gregor (Frontiers in Veterinary Science, 2020)
Canine cognitive dysfunction (CCD) is an age-related disorder similar to human Alzheimer’s disease (AD) that occurs in elderly dogs. Nitrosative stress has been implicated as one of the causes leading to neurodegenerative diseases, particularly AD. Its involvement in the development of CCD has not been studied so far. In the present study, immunohistochemical staining detected all three isoforms of nitric oxide synthases (nNOS, eNOS, and iNOS) and 3-nitrotyrosine (3-NT) in brains from CCD affected dogs and non-demented control dogs in all layers of the canine frontal cortex. In CCD-affected and non-demented brains, nNOS was highly expressed in pyramidal-like neurons in the upper cortical layers. nNOS has also been observed in astrocytes in CCD frontal cortex. The nNOS immunohistochemical staining was statistically significantly elevated in dogs with CCD in comparison to non-demented dogs. Blood vessel wall cells were positive for eNOS, which was also expressed in astrocytes and neurons. Intense 3-NT immunoreactivity was observed in the upper cortical layers, where amyloid-beta deposits spread in the last stage of CCD. Brain cells in the same area were highly immunoreactive for iNOS. This infers that neuroinflammation and nitrosative stress might exacerbate the neurodegenerative process in CCD-affected brains, ultimately leading to cognitive impairment.